1973
DOI: 10.1172/jci107437
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Primary ADP-Induced Platelet Aggregation in Normal Subjects after Administration of Nitrofurantoin (Furadantin)

Abstract: A B S T R A C 'r The evidence indicating that platelets may play a role in the occurrence of certain thromboembolic phenomena has stimulated a search for inhibitors of platelet function. This report presents data to indicate that nitrofurantoin is a potent inhibitor of primary ADP-induced platelet aggregation. The addition of 10 SKI nitrofurantoin to citrated platelet-rich plasma obtained from 12 normal subjects produced a p9946% (2 SD) inhibition of the velocity of platelet aggregation induced by 2 IAIM ADP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1976
1976
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…The most common drugs interfering with platelet membrane function or receptors are amitriptyline (Elavil), 123 imipramine (Tofranil), 124 doxepin (Sinequan), 125 chlorpromazine (Thorazine), 126 cocaine, 127 lidocaine (Xylocaine), 128 isoproterenol (Isuprel), 129 propranolol, 130 cephalothin (Keflin), 131 ampicillin, 132 carbenicillin, 133 penicillin, 134 diphenhydramine (Benadryl), 135 promethazine (Phenergan), 136 and alcohol. Other drugs inducing platelet dysfunction by this mechanism are phentolamine (Regitine), 137 phenoxybenzamine (Dibenzyline), 137 reserpine, 138 dihydroergotamine, 139 desipramine (Norpramine), 124 nortryptyline (Aventyl), 124 trifluoroperazine (Stelazine), 140 procaine, 140 dibucaine (Nupercaine), 141 nitrofurantoin (Furadantin), 142 nafcillin, 143 moxalactam, 144 ticarcillin, 145 dextran, 146 and hydroxyethyl starch. 147…”
Section: Drugs Interfering With Platelet Membrane Receptorsmentioning
confidence: 99%
“…The most common drugs interfering with platelet membrane function or receptors are amitriptyline (Elavil), 123 imipramine (Tofranil), 124 doxepin (Sinequan), 125 chlorpromazine (Thorazine), 126 cocaine, 127 lidocaine (Xylocaine), 128 isoproterenol (Isuprel), 129 propranolol, 130 cephalothin (Keflin), 131 ampicillin, 132 carbenicillin, 133 penicillin, 134 diphenhydramine (Benadryl), 135 promethazine (Phenergan), 136 and alcohol. Other drugs inducing platelet dysfunction by this mechanism are phentolamine (Regitine), 137 phenoxybenzamine (Dibenzyline), 137 reserpine, 138 dihydroergotamine, 139 desipramine (Norpramine), 124 nortryptyline (Aventyl), 124 trifluoroperazine (Stelazine), 140 procaine, 140 dibucaine (Nupercaine), 141 nitrofurantoin (Furadantin), 142 nafcillin, 143 moxalactam, 144 ticarcillin, 145 dextran, 146 and hydroxyethyl starch. 147…”
Section: Drugs Interfering With Platelet Membrane Receptorsmentioning
confidence: 99%
“…Their importance has also been suggested in mouse models of drug-induced liver injury (Chauhan et al ., 2020; Miyakawa et al ., 2015). A literature survey indicated that the two compounds inhibit platelet aggregation (Rossi and Levin, 1973; Slevin et al ., 2018). In addition, the biochemical values of blood in the database showed a slight trend toward an increase in platelet concentration at 9 h compared with the other clusters ( Supplementary Figure S11 ).…”
Section: Resultsmentioning
confidence: 99%
“…This includes but is not limited to septic embolization, central venous and foley catheter infections, graft infections or failures, sepsis, meningococcemia, systemic lupus erythematosus, or vasculitis. 5 …”
Section: Discussionmentioning
confidence: 99%